Self-Medication With Antibiotics By The People Of East Mamungaa Village - RIKWAN Rikwan; Athia Kurnia Kasim; A. Moh Whisnu Suryadinata; Desy Safitri S.A Belike; Ciciliya Gunibala (LPPM Akafarma Sunan Giri Ponorogo, 2025)
The unsupervised use of antibiotics continues to be a pressing public health issue because it may contribute to antimicrobial resistance and increase the likelihood of unwanted health effects. A community’s understanding of when and how antibiotics should be used is one factor that can influence self-medication practices. For this reason, research sought for eva;uatng level knowledge related to independent antibiotic use among residents of East Mamungaa Village. A quantitative descriptive observational approach was selected as it enables a clear depiction of knowledge patterns within the population. A total of 172 individuals 18–65 years asked by purposive sampling, and information was obtained using a structured questionnaire assessing knowledge of indications, safety considerations, and appropriate antibiotic use. The results indicate that 60.5% of participants possessed a moderate level of knowledge, 28.5% demonstrated a good level of knowledge, and 11.0% showed limited knowledge. These outcomes reveal that although most respondents have a basic awareness of antibiotics, important gaps remain—especially in recognizing the dangers of using these medications without clinical guidance. Accordingly, continuous community-based education efforts are needed to strengthen proper antibiotic practices and minimize the risks associated with self-medication.